Opisthorchis viverrini, Clonorchis sinensis and Opisthorchis felineus liver flukes affect mammalian host microbiome in a species-specific manner. - Maria Y Pakharukova; Ekaterina A Lishai; Oxana Zaparina; Nina V Baginskaya; Sung-Jong Hong; Banchob Sripa; Viatcheslav A Mordvinov (PLoS Neglected Tropical Diseases, 2023)
Background Opisthorchis felineus, Opisthorchis viverrini and Clonorchis sinensis are epidemiologically significant food-borne trematodes endemic to diverse climatic areas. O. viverrini and C. sinensis are both recognized to be 1A group of biological carcinogens to human, whereas O. felineus is not. The mechanisms of carcinogenesis by the liver flukes are studied fragmentarily, the role of host and parasite microbiome is an unexplored aspect. Methodology/principal findings Specific pathogen free Mesocricetus auratus hamsters were infected with C. sinensis, O. viverrini and O. felineus. The microbiota of the adult worms, colon feces and bile from the hamsters was investigated using Illumina-based sequencing targeting the prokaryotic 16S rRNA gene. The analysis of 43 libraries revealed 18,830,015 sequences, the bacterial super-kingdom, 16 different phyla, 39 classes, 63 orders, 107 families, 187 genera-level phylotypes. O. viverrini, a fluke with the most pronounced carcinogenic potential, has the strongest impact on the host bile microbiome, changing the abundance of 92 features, including Bifidobacteriaceae, Erysipelotrichaceae, [Paraprevotellaceae], Acetobacteraceae, Coriobacteraceae and Corynebacteriaceae bacterial species. All three infections significantly increased Enterobacteriaceae abundance in host bile, reduced the level of commensal bacteria in the gut microbiome (Parabacteroides, Roseburia, and AF12). Conclusions/significance O. felineus, O. viverrini, and C. sinensis infections cause both general and species-specific qualitative and quantitative changes in the composition of microbiota of bile and colon feces of experimental animals infected with these trematodes. The alterations primarily concern the abundance of individual features and the phylogenetic diversity of microbiomes of infected hamsters.